An examination of the psychometric properties of the Gameful Experience Questionnaire (GAMEFULQUEST) in an online training environment - Booysen, Nicóle (Stellenbosch : Stellenbosch University, 2022)
Thesis (MCom)--Stellenbosch University, 2022.